REVIVAL OF LOCAL RELIGION: A Challange for Church and National Life in Indonesia - Ebenhaezer I. Nuban Timo; Edim Bahabol; Bobby Kurnia Putrawan (Scriptura Indonesia, 2020)
The decision of the Constitutional Meaning of Indonesia that extends the Almighty God Believers to include their identity on the Identity Card is a challenge as well as new opportunities for living together with religions, including for political and religious life. This article reviews the problem in four points. First, regarding the impact of the revival of local religions on the church's understanding of itself and also the task of its witness. Second, how this new reality is responded to by theological schools. Third, the impact of the revival for the life of the nation The fourth point examines how the government should behave towards the phenomenon of religious radicalism and also the response of civil society to the phenomenon.